Clinical relevance of midline fluid percussion brain injury: Acute deficits, chronic morbidities and the utility of biomarkers. (18th September 2016) - Lifshitz, Jonathan; Rowe, Rachel K.; Griffiths, Daniel R.; Evilsizor, Megan N.; Thomas, Theresa C.; Adelson, P. David; McIntosh, Tracy K.
Abstract: Background : After 30 years of characterisation and implementation, fluid percussion injury (FPI) is firmly recognised as one of the best-characterised reproducible and clinically relevant models of TBI, encompassing concussion through diffuse axonal injury (DAI). Depending on the specific injury parameters (e.g. injury site, mechanical force), FPI can model diffuse TBI with or without a focal component and may be designated as mild-to-severe according to the chosen mechanical forces and resulting acute neurological responses. Among FPI models, midline FPI may best represent clinical diffuse TBI, because of the acute behavioural deficits, the transition to late-onset behavioural morbidities and the absence of gross histopathology. Review : The goal here was to review acute and chronic physiological and behavioural deficits and morbidities associated with diffuse TBI induced by midline FPI. In the absence of neurodegenerative sequelae associated with focal injury, there is a need for biomarkers in the diagnostic, prognostic, predictive and therapeutic approaches to evaluate outcomes from TBI. Conclusions : The current literature suggests that midline FPI offers a clinically-relevant, validated model of diffuse TBI to investigators wishing to evaluate novel therapeutic strategies in the treatment of TBI and the utility of biomarkers in the delivery of healthcare to patients with brain injury.